2007
DOI: 10.1007/s10658-006-9077-5
|View full text |Cite
|
Sign up to set email alerts
|

PCR-based determination of colonization patterns during potato tuber infection by single and multiple pathogens

Abstract: Potato tubers piled in storage are prone to infection by numerous pathogens. Each pathogen can cause damage alone, but severe losses often arise when more than one pathogen is involved. Currently, only a visual diagnosis is practiced on potato tubers before storing them, which does not allow any prediction of further disease spread. The aim of the present study was to determine differences in patterns of tissue colonization by several tuber decay pathogens and how late blight infection affects further tuber co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Antagonistic interactions between phytoparasitic fungi have previously been reported in other host-pathogen species pairs [23], as detailed in the Introduction. In many of those studies, the molecular DNA tracing proved to be an essential research tool [25,27,42]. An example that is very similar to the current research is one of the most documented antagonisms among root pathogens, the suppression of Cochliobolus sativus by Fusarium (roseum) species [42].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Antagonistic interactions between phytoparasitic fungi have previously been reported in other host-pathogen species pairs [23], as detailed in the Introduction. In many of those studies, the molecular DNA tracing proved to be an essential research tool [25,27,42]. An example that is very similar to the current research is one of the most documented antagonisms among root pathogens, the suppression of Cochliobolus sativus by Fusarium (roseum) species [42].…”
Section: Discussionsupporting
confidence: 56%
“…A recent meta-analysis suggests that these interactions are probably much more prevalent than previously estimated [23]. Reports on pathogen-pathogen antagonisms encompass diverse plant disease systems, including tree pathogens and wood-rotting fungi [24], storage-rotting fungi [25], foliar pathogens [26], and root rots [27]. Studies of foliar pathogens are most common, with antagonisms being reported among foliar pathogens of wheat, barley, and peas (see, for example, [26,28,29]).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis suggests that these interactions are probably much more prevalent than previously appreciated (Stephens et al 2013). Reported pathogen-on-pathogen antagonisms encompass a diverse cross section of plant disease systems, including tree pathogens and wood rotting fungi (Boddy 2000;Gibbs and Smith 1978), storage rotting fungi (El Hadrami et al 2007;Yang et al 2008), foliar pathogens (Le May et al 2009;Nolan et al 1999), and root rots (Ledingham 1942;Moya-Elizondo et al 2011a;Scardaci and Webster 1981). Studies of foliar pathogens appear most common, with antagonisms reported among foliar pathogens of wheat, barley, and pea (da Luz and Bergstrom 1987;Le May et al 2009;Nolan et al 1999;Round and Wheeler 1978).…”
mentioning
confidence: 99%